Proceedings of the Twenty-Second IEEE/ACM International Conference on Automated Software Engineering 2007
DOI: 10.1145/1321631.1321711
|View full text |Cite
|
Sign up to set email alerts
|

Model-driven derivation of product architectures

Abstract: Product Derivation is one of the central activities in Software Product Lines (SPL). One of the main challenges of the process of product derivation is dealing with complexity, which is caused by the large number of artifacts and dependencies between them. Another major challenge is maximizing development efficiency and reducing time-to-market, while at the same time producing high quality products. One approach to overcome these challenges is to automate the derivation process. To this end, this paper focuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…These relationships can be expressed using general purpose model transformation languages, such as demonstrated in [10][11]. Nevertheless, as previously discussed in [10], these have the following shortcomings: -Metamodel Burden.…”
Section: Managing Variability Using Target-model-specific Languagesmentioning
confidence: 99%
See 2 more Smart Citations
“…These relationships can be expressed using general purpose model transformation languages, such as demonstrated in [10][11]. Nevertheless, as previously discussed in [10], these have the following shortcomings: -Metamodel Burden.…”
Section: Managing Variability Using Target-model-specific Languagesmentioning
confidence: 99%
“…Ziadi et al [10] and Botterweck et al [11] both propose the implementation of product derivation processes as model transformations. Their proposal relies on the realization of product derivations via a model transformation language.…”
Section: Related Wor Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies concerned with the derivation (e.g., [14], [61]) and/or evaluation of software architectures from several points of view (e.g., [65], [37], [70], [66]) have been proposed in literature. After reviewing these studies, we have observed that: (a) There is a lack of systematic methods that model the impact between architectural design decisions and quality attributes to support the integrated derivation, evaluation and quality enhancement of software architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Although several methods for architecture derivation and improvement in SPL development have been proposed over the last few years (e.g., [23], [28], [19], [31], [6], [8], [29]), there is still a need for approaches that model the impact between architectural design decisions and quality attributes and use this information to enhance the quality attribute levels of product architectures. We have addressed this problem, in previous works [17] [18] [20], by proposing an approach with which to ensure the desired quality attribute levels for a product by applying architectural transformations to a product architecture derived from a product line architecture using a multimodel.…”
Section: Introductionmentioning
confidence: 99%